Answer:
Hope this helps
Step-by-step explanation:
72 - 75 = 4
76 - 79 = 3
80 - 83 = 5
84 - 87 = 1
88 - 91 = 3
Which of the equations is graphed below?
(A) y = -2x + 1/2
(B) y = -2x - 1
(C) y = -2x - 1/2
(D) y = -2x + 1
What is the value of x that makes 4(2x + 22.2) = 4(x – 17.87) true?
x=4.33
X=-13.36
O
Ob
Ос
Od
X=-40.07
x=40.07
Answer:
try youre best to complete youre succsess
please help me I will give brainliest
Answer:
c is the answer
Step-by-step explanation:
your welcome
Part B
Find the equation of a line passing through the same point that f(x) passes through at x = 3 with a slope equal to the limit
you found in part A.
the equation in part A is x^3-4x^2+2 and when x=3 y=-7 so, (3,-7) is the point the equation for part B needs to pass through
The linear equation that has a slope of -7 and crosses the x-axis at (3, 0) is:
y = -7x + 21
How to find the linear equation?
A general linear equation is:
y = a*x +b
Where a is the slope and b is the y-intercept.
The slope must be equal to the limit found in part a, and you say that it is equal to -7, so the slope is -7. And for how is written the problem, I understand that it crosses the x-axis at x = 3.
Then we will have:
y = -7*x + b
Such that, when x = 3, y = 0, then:
0 = -7*3 + b
21 = b
Then the linear equation is y = -7x + 21
If you want to learn more about linear equations:
https://brainly.com/question/1884491
#SPJ1
Answer:
The line will pass through (3,-7) and has a slope of 3
Step-by-step explanation:
x=3 , f(x) = x^3 - 4x^2 + 2
f(3) = 3^3 -4(3)^2 + 2
f(3) = -7
Find the radius of the circle in which the central angle arc=3 intercepts an arc of length is =6ft.
Answer: 2
Step-by-step explanation:
SEE IMAGE PLEASE !!!
Answer:
A. 38
Step-by-step explanation:
Diagonals of a rhombus bisect 90° at the center. Taking O to be the center :
90° + x° + (x +14)° = 180° [Angle Sum Property]2x + 104 = 1802x = 76x = 38Option ASolve for the value of x :-
5(x+4)+5(2-x)
Answer:
[tex]30[/tex]
Step-by-step explanation:
Given expression:
[tex]5(x + 4) + 5(2 - x)[/tex]
Note: The value of "x" is undefined because the given sum is not an equation. Thus, I will simplify the expression as much as possible.
Let us simplify all the distributive properties stated in the expression.
Apply the distributive property rule [a(b + c) = ab + ac]
[tex]\implies5(x) + 5(4) + 5(2) - 5(x)[/tex]
Since 5(x) is being subtracted from 5(x), we get:
[tex]\implies 5(x) + 5(4) + 5(2) - 5(x)[/tex]
[tex]\implies 5(4) + 5(2)[/tex]
Finally, let us simplify the sum of the product of (5 and 4) and (5 and 2).
[tex]\implies20 + 10[/tex]
[tex]\implies \boxed{30}[/tex]
Learn more about one-variable expressions: https://brainly.com/question/15139917
A circle has an area of 20cm. What is its diameter?
Answer:
should be 5.05
Step-by-step explanation:
rounded to nearest hundredth
Answer:
5.02
Step-by-step explanation:
Formula for area= π x r^2
(π is 3.14)
Formula for diameter= 2 x r
So all you basically have to do is go backwords with the first equation
20/π=6.36
Now you have 6.36, though you need to go even further back because of the ^2
√6.36=2.51
Now we have the radius, so stick that into the diameter formula
2 x 2.51
5.02 is the diameter :)
Which graph represent y as a function of x
A answer number 1 please
Answer:
Number one is not reasonable
I NEED HELP! ASAP, THIS IS SO HARD AND MY BRAIN HURTS, IF U HELP ME WITH OTHER QUESTIONS LIKE THIS ILL GIVE U 50+ POINTS
Let O be an angle in quadrant III such that cos 0 = -2/5 Find the exact values of csco and tan 0.
well, we know that θ is in the III Quadrant, where the sine is negative and the cosine is negative as well, or if you wish, where "x" as well as "y" are both negative, now, the hypotenuse or radius of the circle is just a distance amount, so is never negative, so in the equation of cos(θ) = - (2/5), the negative must be the adjacent side, thus
[tex]cos(\theta)=\cfrac{\stackrel{adjacent}{-2}}{\underset{hypotenuse}{5}}\qquad \textit{let's find the \underline{opposite side}} \\\\\\ \textit{using the pythagorean theorem} \\\\ c^2=a^2+b^2\implies \sqrt{c^2-a^2}=b \qquad \begin{cases} c=hypotenuse\\ a=adjacent\\ b=opposite\\ \end{cases} \\\\\\ \pm\sqrt{5^2 - (-2)^2}=b\implies \pm\sqrt{25-4}\implies \pm\sqrt{21}=b\implies \stackrel{III~Quadrant}{-\sqrt{21}=b}[/tex]
[tex]\dotfill\\\\ csc(\theta)\implies \cfrac{\stackrel{hypotenuse}{5}}{\underset{opposite}{-\sqrt{21}}}\implies \stackrel{\textit{rationalizing the denominator}}{-\cfrac{5}{\sqrt{21}}\cdot \cfrac{\sqrt{21}}{\sqrt{21}}\implies -\cfrac{5\sqrt{21}}{21}} \\\\\\ tan(\theta)=\cfrac{\stackrel{opposite}{-\sqrt{21}}}{\underset{adjacent}{-2}}\implies tan(\theta)=\cfrac{\sqrt{21}}{2}[/tex]
PLEASE HELP !!!! I WILL GIVE BRAINLISET ! Find the volume of the sphere.
Either enter an exact answer in terms of pi or use 3.14, for π and round your final answer to the nearest hundredth.
Step-by-step explanation:
Volume = 4πr³/3
= 4•7³•π/3
=1372π/3
= 1372•3.14/3
≈ 1436.03 units³
to the nearest hundredth.
What is the quotient of 28,435÷47?
add the term that makes the given expression into a perfect square write the result as the square of a bracketed expression a square + 8a
Answer:
see explanation
Step-by-step explanation:
a² + 8a
using the method of completing the square
add ( half the coefficient of the a- term)²
a² + 2(4)a + 16
= (a + 4)²
If k=
t-5k
and k= 4, what is the value of t?
A) -28
B) -12
C) 12
D) 28
Answer:
24
Step-by-step explanation:
k = t - 5k
→ Substitute in k
4 = t - 20
→ Add 20 to both sides
24 = t
Given C is the midpoint of line AB, D is the midpoint of line AC, and E is the midpoint of line DC. If AE=16, what is DB?
Answer:
DB = 32
Step-by-step explanation:
Given :
⇒ C is the midpoint of the line AB
⇒ E is the midpoint of the line DC
⇒ AE = 16
=============================================================
Understanding :
⇒ AC = BC = 1/2AB
⇒ AD = DC = 1/2AC = 1/4AB
⇒ DE = 1/2AD = 1/4AC = 1/8AB
=============================================================
Finding AB :
⇒ AE = AD + DE
⇒ 16 = 1/4AB + 1/8AB
⇒ 3/8AB = 16
⇒ AB = 16 x 8 / 3
⇒ AB = 128/3
=============================================================
Finding DB :
⇒ DB = DC + CB
⇒ DB = 1/4AB + 1/2AB
⇒ DB = 3/4AB
⇒ DB = 3/4 × 128/3
⇒ DB = 128/4
⇒ DB = 32
Determine the equation of the elastic curve for the beam using the x1 coordinate for 0 ≤ x1 ≤ l/2
The elastic curve between 0 to L/2 is a cubic curve. And the elastic curve is shown in the given diagram.
What is an elastic curve?The flexible curve of a beam is the curve generated by the crossover of the horizontal member with the beam's side, with continuous stresses on the fibers considered to be within the elastic limit.
The slope at L/2 will be
[tex]\rm \theta _{L/2} = \dfrac{PL^2}{8EI}[/tex]
The deflection of the beam at L/2 will be
[tex]\rm y_{L/2} = \dfrac{P(L/2)^3}{3EI}\\\\\rm y_{L/2} = \dfrac{PL^3}{24EI}[/tex]
And the deflection of the beam at L will be
[tex]\rm y_{L} = \dfrac{PL^3}{24EI} + \dfrac{L}{2} \times \theta _{L/2} \\\\\rm y_{L} = \dfrac{PL^3}{24EI} + \dfrac{L}{2} \times \dfrac{PL^2}{8EI}\\\\\rm y_{L} = \dfrac{5PL^3}{48EI}[/tex]
Then the elastic curve will be shown in the diagram.
More about the elastic curve link is given below.
https://brainly.com/question/24230581
#SPJ4
The Cooper family drove 987.6 miles on their vacation. They drove the same number of miles each day. If the trip was 6 days, how many miles did they drive each day?
Answer:
164.6
Step-by-step explanation: i'm a human calculator
Answer:
164.6
Step-by-step explanation:
Divide 987.6 by 6 = 987.6/6= 164.6
Let x be a real number satisfying the condition : √x²-9 · √x²-1 = 2x+3
Calculate the expression value : Q = √x²-1 · √x^2-4 - 3x
Answer:
x= 2
1 =0.5
x=0
Step-by-step explanation:
Find the value of x. (‼️‼️‼️‼️
Answer: 5
Step-by-step explanation:
Solve for the value of x.
Answer:
x=4
Step-by-step explanation:
Given M is the midpoint
We know that midpoint of a line divides the line into two equal parts
Therefore on equating we get
[tex]4x + 1 = 8x - 15[/tex]
[tex]1 + 15 = 8x - 4x[/tex]
[tex]16 = 4x[/tex]
[tex]x = 4[/tex]
Steps:
[tex]4x+1= 8x-15[/tex]
=>subtract 4 on both sides with 8x
[tex]1=4x-15[/tex]
=>now do add 15 both sides
[tex]16=4x[/tex]
=>Now divide 4x both sides
[tex]\frac{16}{4} =\frac{4x}{4}[/tex]
[tex]4=x[/tex]
So 4 is the answer
☆( O u O ) ☆
╔uu══════════════════╗☆
❝ carry on learning. ❞
╚══════nn════════════╝
A whale is at the surface of the ocean tto breathe. What is the whale's elevation? Draw a numhber line
Answer:0
<—————|—————>
0
Step-by-step explanation:
Find mPQ in the circle to the right
What does x equal with this equation
x/6-33= -27
Answer:
The first thing that we have to do is add 33 to both sides to try to reduce the amount of variables on the left hand side.
[tex]\frac{x}{6} - 33 = -27[/tex]
[tex]\frac{x}{6} - 33 + 33 = -27 + 33[/tex]
[tex]\frac{x}{6} = 6[/tex]
Now that we have simplified the left hand side even more we only have one part left to get x by itself which is to multiply both sides by 6.
[tex]\frac{x}{6} = 6[/tex]
[tex]\frac{x}{6} * 6 = 6 * 6[/tex]
[tex]x = 36[/tex]
Therefore, our final answer for what the value of x equals is 36.
Hope this helps! Let me know if you have any questions
help me here plss Fast
1. and 2. thanks ^^
Step-by-step explanation:
here you go hope it helps
Completely factor the given polynomial: 2x^2 - 8x - 10
Answer:
2(x - 5)(x + 1)
Step-by-step explanation:
2x² - 8x - 10 ← factor out 2 from each term
= 2(x² - 4x - 5) ← factor the quadratic
consider the factors of the constant term (- 5) which sum to give the coefficient of the x- term (- 4)
the factors are - 5 and + 1 , since
- 5 × 1 = - 5 and - 5 + 1 = - 4 , then
x² - 4x - 5 = (x - 5)(x + 1)
then
2x² - 8x - 10 = 2(x - 5)(x + 1) ← in factored form
Answer: [tex]2(x-1)(x+5)[/tex]
Step-by-step explanation:
Factor [tex]2[/tex] out of [tex]2x^2[/tex] [tex]+~8x-10[/tex]
[tex]Factor[/tex] [tex]2 ~out~ of ~2x^2[/tex]:
[tex]2(x^2)+8x-10[/tex]
[tex]Factor ~2~ out ~of ~8x[/tex]:
[tex]2(x^2)+2(4x)-10[/tex]
[tex]Factor ~2~ out~ of ~-10[/tex]:
[tex]2x^2+2(4x)+2~x~-5[/tex]
[tex]Factor ~2~ out~ of ~2x^2+2(4x):[/tex]
[tex]2(x^2+4x)+2[/tex] × [tex]-5[/tex]
[tex]Factor ~2~out ~of ~2(x^2+4x)+2[/tex] × [tex]-5:[/tex]
[tex]2(x^2+4x-5)[/tex]
factor:
[tex]Factor ~x^2+4x-5~ using ~the ~AC~ method.[/tex]
Consider the form [tex]x^2+bx+c.[/tex] Find a pair of integers whose product is [tex]c[/tex] and whose sum is [tex]b[/tex]. In this case, whose product is [tex]-5[/tex] and whose sum is [tex]4.[/tex]
[tex]-1,5[/tex]
Write the factored form using these integers.
[tex]2((x-1)(x+5))[/tex]
Remove unnecessary parentheses.
[tex]=2(x-1)(x+5)[/tex] ← final answer
A die is rolled 117 times with the results in the table below.
What is the experimental probability of rolling a 5 with this die?
Answer:
19/117
Step-by-step explanation:
Because the dice did land on 5, 19 times out of 117
If a1= 3 and an= 2an-1 then find the value of 06.
Answer:
a₆ = 96
Step-by-step explanation:
assuming you mean find a₆
using the recursive rule and a₁ = 3 , then
a₂ 2a₁ = 2 × 3 = 6
a₃ = 2a₂ = 2 × 6 = 12
a₄ = 2a₃ = 2 × 12 = 24
a₅ = 2a₄ = 2 × 24 = 48
a₆ = 2a₅ = 2 × 48 = 96
6 2+8×3=
btw the two is supposed to be above the 6 like if you said 6 to the second power
Answer:
60
Step-by-step explanation:
(* = multiplication symbol)
6^2+8*3
36+8*3
36+24
60
Answer:60
Step-by-step explanation:
Use bidmas
(Brackets Indices Division Multiplication Addition Subtraction)
so first do 6 squared =36
Then 8x3 =24
Then 36+24= 60